A new method for combining detrending techniques with application to business cycle sychchronization of the new EU members - Zsolt Darvas; Gábor Vadas (Magyar Nemzeti Bank, 2005)
Decomposing output into trend and cyclical components is an uncertain exercise and depends on the method applied. It is an especially dubious task for countries undergoing large structural changes, such as transition countries. Despite their deficiencies, however, univariate detrending methods are frequently adopted for both policy oriented and academic research. This paper proposes a new procedure for combining univariate detrending techniques which is based on revisions of the estimated output gaps adjusted by the variance of and the correlation among output gaps. The procedure is applied to the study of the similarity of business cycles between the euro area and new EU Member States.
Keywords: C22; E32; 330; combination; detrending; new EU members; OCA; output gap; revision; Konjunktur; Gesamtwirtschaftliche Produktion; Zeitreihenanalyse; Schätzung; Kroatien; Russland; EU-Staaten (Osteuropa)